2018
DOI: 10.5505/kpd.2018.37450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ganglion cell layer thickness in children with attention deficit hyperactivity disorder and comorbid oppositional defiant disorder (eng)

Abstract: Evaluation of the ganglion cell layer thickness in children with attention deficit hyperactivity disorder and comorbid oppositional defiant disorder Gangliyon hücre tabakasý kalýnlýðýnýn dikkat eksikliði hiperaktivite bozukluðu ve komorbid karþýt olma karþý gelme bozukluðu olan çocuklarda deðerlendirilmesi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…5 In another study, Bodur et al compared RNFL thickness, ganglion cell layer (GCL), and optic nerve thickness in patients with ADHD, ADHD plus oppositional defiant disorder (ODD), and controls. 15 The authors found no difference in RNFL thickness between the groups, but significantly lower GCL and optic nerve thickness in the patient groups than in controls. 15 The abovementioned studies examining the relationship between OCT and ADHD only included ADHD and control groups; to date, no studies have compared drugtreated ADHD patients, drug-naive ADHD patients, and healthy controls.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…5 In another study, Bodur et al compared RNFL thickness, ganglion cell layer (GCL), and optic nerve thickness in patients with ADHD, ADHD plus oppositional defiant disorder (ODD), and controls. 15 The authors found no difference in RNFL thickness between the groups, but significantly lower GCL and optic nerve thickness in the patient groups than in controls. 15 The abovementioned studies examining the relationship between OCT and ADHD only included ADHD and control groups; to date, no studies have compared drugtreated ADHD patients, drug-naive ADHD patients, and healthy controls.…”
Section: Introductionmentioning
confidence: 85%
“…10,11 For centuries, the retina has been known to provide insight into the status of the brain, suggesting the suitability of retinal research to explore bipolar disorder, schizophrenia, major depressive disorder, and ADHD. 5,[12][13][14][15] Optical coherence tomography (OCT) is a comparatively new, noninvasive, and contactless imaging technique that was first used in the field of ophthalmology. 16 The use of OCT to study axonal structural abnormalities has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with the previous result, we found RNFL thickness was lower in the ADHD group than in the control group, but this difference was not statistically significant. In the other study, children and adolescents with ADHD and Oppositional Defiant Disorder (ODD) accompanying ADHD compared to healthy controls, no significant difference was found in terms of RNFL but the ganglion cell layer of the retina was found to be thinner in ADHD and ADHD + ODD groups [21].…”
Section: Discussionmentioning
confidence: 85%
“…Hergüner et al found that the ADHD group's macular thickness did not differ from age-matched controls, but the RNFL thickness is reduced in the ADHD group [20]. In another study, children and adolescents with ADHD and Oppositional Defiant Disorder (ODD) accompanying ADHD compared to healthy controls, no significant difference was found in terms of RNFL but the ganglion cell layer of the retina was found to be thinner in ADHD and ADHD + ODD groups [21].…”
Section: Introductionmentioning
confidence: 97%